1981
DOI: 10.1021/bi00528a029
|View full text |Cite
|
Sign up to set email alerts
|

Activation and chromatographic properties of the AtT-20 mouse pituitary tumor cell line glucocorticoid receptor

Abstract: The physicochemical properties of the glucocorticoid receptor (GC-R) from the mouse AtT-20 pituitary tumor cell line were studied. Analyses involved ion-exchange (diethylaminoethylcellulose, phosphocellulose), gel filtration (Sephadex G-150), and adsorption (DNA-cellulose, hydroxylapatite) chromatography. The receptor was characterized in four different states: native (unactivated), activated, nuclear, and Na2Mo04 stabilized. The unactivated receptor had chromatographic properties which were very similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…The mouse AtT-20 pituitary tumor cell line was maintained in T flasks and spinner suspension culture as described previously (Vedeckis, 1981). When not used for purification, GC-R prepared in TETg (20 mM Tris-HCl, 1 mM EDTA, 12 mM 1-thioglycerol, pH 7.4 at 22 °C) buffer was labeled with 3 X 10-* M [3H]TA overnight at 0-4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse AtT-20 pituitary tumor cell line was maintained in T flasks and spinner suspension culture as described previously (Vedeckis, 1981). When not used for purification, GC-R prepared in TETg (20 mM Tris-HCl, 1 mM EDTA, 12 mM 1-thioglycerol, pH 7.4 at 22 °C) buffer was labeled with 3 X 10-* M [3H]TA overnight at 0-4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…binding moiety f reviewed in Vedeckis (1985)]. Our laboratory has performed a detailed series of studies to elucidate the structure of the glucocorticoid receptor (GC-R)1 *in the mouse AtT-20 pituitary tumor cell line (Vedeckis, 1981(Vedeckis, , 1983aEastman-Reks et al, 1984;Reker et al, 1985;Kovacic-Milivojevic et al, 1985;Vedeckis et al, 1985). We 1 Abbreviations: 94K, 24K, etc., M, of 94000, 24000, etc.…”
mentioning
confidence: 99%
“…From (32) kind of reduction must be occurring. Transformation of the glucocorticoid-receptor complex caused by salt or by precipitation with ammonium sulfate also is inhibited by molybdate (42,95), as is salt-mediated transformation of progesterone receptor and estrogen receptor (66,74).…”
Section: Effects Of Molybdate On the Stability Of Unbound Receptorsmentioning
confidence: 99%
“…In addition to inhibiting transformation of glucocorticoid-and estrogen bound receptors, molybdate prevents the shift of these complexes to a less negatively charged state that occurs during DEAE-cellulose chromatography (17,74,95). (42) found that molybdate inhibited inactiva tion and transformation of glucocorticoid receptors caused by salt or ammo nium sulfate precipitation at 0°-4 °C.…”
Section: Effects Of Molybdate On the Stability Of Unbound Receptorsmentioning
confidence: 99%
“…Cell Culture. AtT-20 cells were grown in Dulbecco's modified Eagle's medium F12 (DMEM F12, GIBCO, Grand Island, NY) supplemented with 10% newborn calf serum (Bio Whittaker, Walkersville, MD) as previously described (Vedeckis, 1981). L929 mouse fibroblast cells were grown in DMEM/high glucose (GIBCO) supplemented with 10% fetal bovine serum (FBS, Irvine Scientific, Santa Ana, CA).…”
Section: Methodsmentioning
confidence: 99%